A helping hand for Tuaran - Siti Sarah, Mohamad Rajimi (2017)
Seikhlas Kasih Seindah Budi program organized by Students Affairs & Alumni Department (Saffad) and AlFalah Secretariat succeeded in cultivating the spirit of volunteerism to UMP student hence develop social integration between students and Kiulu local community.